Developing effective institutions for water resources management: A case study in the Deduru Oya Basin, Sri Lanka - Somaratne, Pallewatte G.; Jinapala, K.; Perera, L.R.; Ariyaratne, Badugodahewa Ranjith; Bandaragoda, Don Jayatissa; Makin, Ian W. (International Water Management Institute, 2003)
This report is based on a research project financed by the Asian Development Bank (ADB) to conduct a regional study for the development of effective water management institutions (ADBRETA no 5812). Research activities were conducted in five river basins in Indonesia, the Philippines, Nepal, China and Sri Lanka for a period of three years commencing from 1999. The river basin studied in Sri Lanka was the Deduru Oya river basin in the North Western Province of the country. This report contains the findings of the Deduru Oya basin study. The overall objective of the case study conducted in Sri Lanka was to help the government of Sri Lanka to improve the institutions managing scarce water resources within the frame work of integrated water resources management. This case study included a comprehensive assessment of the existing physical, socio-economic and institutional environment in the river basin and also the long term changes that are likely to take place.